Wachstums- und Verschuldungseffekte einer kreditfinanzierten öffentlichen Investitionsoffensive; Growth and debt effects of a credit-financed public investment offensive - Sebastian Dullien; Ekaterina Jürgens; Christoph Paetz; Sebastian Watzka (Wirtschaftsdienst, 2021)
Öffentliche Investitionen stehen ganz oben auf der wirtschaftspolitischen Agenda in Deutschland. Simulationen mit dem makroökonomischen Mehrländermodell NiGEM zeigen, dass sich ein großes, 460 Mrd. Euro umfassendes, kreditfinanziertes Investitionsprogramm nach spätestens 30 Jahren selbst finanzieren würde. In der Zwischenzeit würden Wirtschaftsleistung und private Investitionstätigkeit deutlich kräftiger ausfallen als ohne solch eine Initiative. – – Simulations of a deficit-financed public investment programme in Germany amounting to exteuro460 billion over ten years in the macroeconomic model NiGEM show that it will finance itself in 30 years at most, even under conservative model assumptions. In the basic version of the model, GDP is 3 % to 4 % above the baseline in the long run. Additionally, private investment is stimulated and rises by 4 % to 5 % above the baseline. These effects are amplified when an increase in the productivity of the private capital stock due to improved public infrastructure is taken into account.
Keywords: C5; E6; H5; H6; 330; Öffentliche Investition; Wirtschaftspolitik; Deutschland